The implementation of problem-based laboratory model at digital signal processing laboratory - Abu Samah, Narina (2014)
This paper describes the implementation of Problem-based Laboratory (PBLab) Model at Digital Signal Processing Laboratory (DSP Lab), Faculty of Electrical Engineering, Universiti Teknologi Malaysia (UTM). The model was developed as an alternative to the conventional instructional based laboratory previously practiced. Grounded in the paradigm of constructivism, the implementation of PBLab model serves as mechanism that enhances construction of knowledge, critical thinking, creativity and transferable skills among engineering undergraduates. A case study is presented to illustrate of undergraduates' problem solving process during PBLab that includes activities and facilitations throughout in-lab and out-lab sessions. Insights from a group interview suggest that problem-based PBLab facilitates undergraduates' higher order thinking skills which include metacognition strategies and transfer of knowledge abilities, as well as generic skills such as intrapersonal/interpersonal communications and team-working skills.